Intercultural Differences as a Condition of Intercultural Understanding - E. Usovskaya (Евразийская интеграция: экономика, право, политика)
The article deals with cultural differences, which are understood as recognition of the unique differences of each culture, expressed in a specific relation to the individual, groups of people and to the world in the form of values, traditions, activities, mentality and behavior. Relevance of the study of cultural differences caused by contradictory social cultural and political situation in modern Europe and the world, the realities of integration and disintegration processes. The article deals with possible ways and prospects of cooperation between Belarus and different cultures and countries, including Russia.